THE ROLE OF PUBLIC RELATIONS IN THE HOSPITAL INDUSTRY - Denisya Susanti; Try Sarmedi Saragih; Utami Pramadianti (Fox Justi : Jurnal Ilmu Hukum, 2020)
This study aims to determine the role of Public Relations in the hospitality industry in managing and maintaining the good image of the hotel. The research instrument used in this research is the method of observation at Grandia Hotel Bandung and giving questionnaires to the staff and Public Relations of Grandia Hotel Bandung. The research method uses a qualitative approach by applying the type of descriptive research, namely from the data that has been collected the researcher tries to draw conclusions. Data analysis techniques include data reduction, data decomposition, and drawing conclusions. The result of this research is that public relations has a duty in shaping the good image of the hotel to the public. With the existence of public relations, the communication that exists is harmonious between the institution and the public by creating good reciprocity. Public relations has two important roles in a company, namely the regulatory function and the supervisory function of a company. Public relations is a very important part in the hospitality industry in creating an image for both internal and external parties. The conclusion of this study is that public relations has an important role in the hospitality industry, namely in creating a positive image of the hotel to the public by maintaining the relationship between the hotel and the public or with other companies becomes more harmonious, and public relations also plays a role in supervising an institution, namely the regulatory function and the supervisory function of a company. Public relations is a very important part in the hospitality industry in creating an image for both internal and external parties. The conclusion of this study is that public relations has an important role in the hospitality industry, namely in creating a positive image of the hotel to the public by maintaining the relationship between the hotel and the public or with other companies becomes more harmonious, and public relations also plays a role in supervising an institution, namely the regulatory function and the supervisory function of a company. Public relations is a very important part in the hospitality industry in creating an image for both internal and external parties. The conclusion of this study is that public relations has an important role in the hospitality industry, namely in creating a positive image of the hotel to the public by maintaining the relationship between the hotel and the public or with other companies becomes more harmonious, and public relations also plays a role in supervising an institution,